Anak Berkebutuhan Khusus (ABK) dalam Perspektif Psikologi Pendidikan Islam - Hartanto, Rudy (TSAQOFAH, 2025)
Islamic religious education plays a vital role in shaping the character, morality, and spirituality of learners, including children with special needs (CWSN), who within the framework of inclusive education have equal rights to receive religious instruction tailored to their psychological development and individual conditions. This study aims to analyze the role of educational psychology in supporting the implementation of adaptive and meaningful Islamic religious education for CWSN. A qualitative literature review method was employed to explore the integration of Islamic values and psychological approaches within the learning process. The findings indicate that individualized approaches, differentiated instruction, the use of multisensory media, and collaboration among teachers, families, and communities contribute to more inclusive religious education practices. However, significant challenges remain, including the shortage of trained educators, the lack of adaptive learning resources, and persistent social stigma, all of which require systemic and collaborative solutions. The study concludes that integrating Islamic values with the principles of educational psychology forms a critical foundation for developing a just, empathetic, and diversity-respecting model of Islamic religious education.